2016
DOI: 10.1002/jsfa.7999
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphate groups on antiviral activity of casein phosphopeptide against feline calicivirus as a surrogate for norovirus

Abstract: The CPP effect was enhanced by the introduction of additional phosphates and conversely weakened by their elimination. Therefore, CPP-III phosphorylation represents an emerging approach for the production of food-grade antiviral agents. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Phosphorylated CPP-III exhibited stronger antiviral activities than its native and dephosphorylated forms. We next demonstrated that the stronger antiviral activities of P-CPP were dependent on the negative electrostatic charge of the phosphate groups attached to the amino acid chain [20]. An overview of recent researches [19] indicated that dietary ingredients, especially immunomodulatory protein hydrolysates, exhibit the capacity to attenuate food allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylated CPP-III exhibited stronger antiviral activities than its native and dephosphorylated forms. We next demonstrated that the stronger antiviral activities of P-CPP were dependent on the negative electrostatic charge of the phosphate groups attached to the amino acid chain [20]. An overview of recent researches [19] indicated that dietary ingredients, especially immunomodulatory protein hydrolysates, exhibit the capacity to attenuate food allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide moieties by nature have long side chains, as such, this might hamper their ability to reach and mask epitopes located at the interior of proteins. The addition of phosphate groups to a protein might not only function as a more effective method to mask the epitope site of allergenic proteins but also as a strong enhancer of immunomodulation as evidenced by its previous promotion of type-I IFN secretion [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate groups play an important role in immunomodulation, for example by promoting type-I IFN secretion. [14] Notably, in a previous study, casein phosphopeptide was shown to yield reduced allergy symptoms by promoting intestinal IgA production and reducing serum IgE levels. [15] The introduction of a phosphate group to allergic proteins might therefore contribute not only to the masking of epitope sites, but also to enhanced immunomodulation.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, we hypothesized that phosphorylation might serve as a more effective method for masking the epitope sites of allergenic proteins. Phosphate groups play an important role in immunomodulation, for example by promoting type‐I IFN secretion . Notably, in a previous study, casein phosphopeptide was shown to yield reduced allergy symptoms by promoting intestinal IgA production and reducing serum IgE levels .…”
Section: Introductionmentioning
confidence: 99%